Cell cycle arrest and apoptosis in TP53 subtypes of bladder carcinoma cell lines treated with cisplatin and gemcitabine - da Silva, Glenda Nicioli [UNESP]; de Castro Marcondes, Joao Paulo [UNESP]; de Camargo, Elaine Aparecida [UNESP]; da Silva Passos Junior, Geraldo Aleixo; Sakamoto-Hojo, Elza Tiemi; Salvadori, Daisy Maria Favero [UNESP] (Soc Experimental Biology Medicine, 2010)
Currently, the combination of cisplatin and gemcitabine is considered a standard chemotherapeutic protocol for bladder cancer. However, the mechanism by which these drugs act on tumor cells is not completely understood. The aim of the present study was to investigate the effects of these two antineoplastic drugs on the apoptotic index and cell cycle kinetics of urinary bladder transitional carcinoma cell lines with wild-type or mutant TP53 (RT4: wild type for TP53; 5637 and T24: mutated TP53). Cytotoxicity, cell survival assays, clonogenic survival assays and flow cytometric analyses for cell cycle kinetics and apoptosis detection were performed with three cell lines treated with different concentrations of cisplatin and gemcitabine. G(1) cell cycle arrest was observed in the three cell lines after treatment with gemcitabine and gemcitabine plus cisplatin. A significant increase in cell death was also detected in all cell lines treated with cisplatin or gemcitabine. Lower survival rates occurred with the combined drug protocol independent of TP53 status. TP53-wild type cells (RT4) were more sensitive to apoptosis than were mutated TP53 cells when treated with cisplatin or gemcitabine. Concurrent treatment with cisplatin and gemcitabine was more effective on transitional carcinoma cell lines than either drug alone; the drug combination led to a decreased cell survival that was independent of TP53 status. Therefore, the synergy between low concentrations of cisplatin and gemcitabine may have clinical relevance, as high concentrations of each individual drug are toxic to whole organisms.
Keywords: apoptosis; cisplatin; gemcitabine; TP53; urinary bladder transitional cell carcinoma